2011
DOI: 10.1021/nn201896m
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Coated NaYF4:Yb3+, Er3+ Upconversion Nanoparticles for Charge-Dependent Cellular Imaging

Abstract: Lanthanide-doped upconversion nanoparticles (UCNPs) are considered promising novel near-infrared (NIR) bioimaging agents with the characteristics of high contrast and high penetration depth. However, the interactions between charged UCNPs and mammalian cells have not been thoroughly studied, and the corresponding intracellular uptake pathways remain unclear. Herein, our research work involved the use of a hydrothermal method to synthesize polyvinylpyrrolidone-coated UCNPs (UCNP-PVP), and then a ligand exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
179
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(182 citation statements)
references
References 57 publications
2
179
0
1
Order By: Relevance
“…Various in vitro (98)(99)(100)(101) and in vivo (102-106) models have been employed to validate the bioimaging potentials of RE UCNs. For example, Li and coworkers (103) synthesized sub-10-nm β-NaLuF 4 :Gd,Yb,Tm UCNs for sensitive in vivo imaging.…”
Section: Applicationsmentioning
confidence: 99%
“…Various in vitro (98)(99)(100)(101) and in vivo (102-106) models have been employed to validate the bioimaging potentials of RE UCNs. For example, Li and coworkers (103) synthesized sub-10-nm β-NaLuF 4 :Gd,Yb,Tm UCNs for sensitive in vivo imaging.…”
Section: Applicationsmentioning
confidence: 99%
“…[176] Auf diese Weise codierte Zellen kçnnen auch in Tiere injiziert werden, um deren zelluläre Dynamik über die Zeit zu verfolgen. Die Gruppe von Wang [177] dotierte aufkonvertierende Nanostäbchen des Typs NaYF 4 :Yb,Er zusätzlich mit La 3+ oder Ce 3+ , um die Emissionsintensitäten einzeln einzustellen.…”
Section: Mehrfarbmarkierung Von Zellen Mit Ucnps Für Die Bildgebungunclassified
“…The crystal field of host materials for UCNPs should facilitate upconversion emission, to achieve the above desired features. The most efficient host material reported thus far is NaYF 4 , with many studies on NaYF 4 UCNPs having been reported (Jin et al, 2011;Yang et al, 2012). NaYF 4 nanoparticles with good upconversion emission have a hexagonal phase structure, while the cubic phase results in poor upconversion emission.…”
Section: Introductionmentioning
confidence: 99%